Lifestyle-related advice in the management of obesity: A step-wise approach - Sakshi Chopra; Anita Malhotra; Piyush Ranjan; Naval K Vikram; Namrata Singh (Wolters Kluwer Medknow Publications, 2020)
Obesity is a commonly encountered health-care problem that is an independent risk factor for chronic metabolic complications. Primary care physicians are the first point of contact in the management of obesity. Weight management is a step-wise intensification of interventions that initiates with lifestyle modification. Dietary and physical activity advices are integral components of all weight loss consultations and should ideally be imparted by a dietician or a nutritionist. In case of their nonavailability, the onus for lifestyle counseling rests with the physician. The prescription for a low-calorie diet coupled with increased physical activity might seem simple, but the success lies in compliance and sustainability of this advice. Compliance can be enhanced through patient-specific diet and activity plans along with corrections in eating and activity behavior. Barriers in patient's environment must also be addressed to achieve sustainable weight loss. This review covers practical insights in standard lifestyle management techniques, which can help the physicians to set better weight loss goals, adapt to patient specific lifestyle counseling, and apply strategies to enhance compliance for sustained weight loss.